2004
DOI: 10.1103/physrevb.69.035338
|View full text |Cite
|
Sign up to set email alerts
|

Conductance distribution in nanometer-sized semiconductor devices due to dopant statistics

Abstract: We show that individual dopant atoms dominate the transport characteristics of nanometer-sized devices, by investigating metal-semiconductor diodes down to 15 nm diameter. Room-temperature measurements reveal a strongly increasing scatter in the device-to-device conductance towards smaller device sizes. The lowtemperature measurements exhibit pronounced features, caused by resonant tunneling through electronic states of individual dopant atoms. We demonstrate by a statistical analysis that this behavior can be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 16 publications
0
14
0
Order By: Relevance
“…First time-resolved EDMR measurements have already been reported [96]. A combination of such experiments where Rabi oscillations can be detected through transport measurements with nanostructures containing a single paramagnetic center such as a dopant [97] or a quantum dot [98] will be a crucial step towards the realization of spinbased quantum computing in semiconductors. The investigation of spin-dependent transport processes in semiconductors is far from complete.…”
Section: Discussionmentioning
confidence: 99%
“…First time-resolved EDMR measurements have already been reported [96]. A combination of such experiments where Rabi oscillations can be detected through transport measurements with nanostructures containing a single paramagnetic center such as a dopant [97] or a quantum dot [98] will be a crucial step towards the realization of spinbased quantum computing in semiconductors. The investigation of spin-dependent transport processes in semiconductors is far from complete.…”
Section: Discussionmentioning
confidence: 99%
“…The microscale contact scaling will result in a reduced depletion width [26]. Leonard et al [4] have shown that in the case of nanocontacts with the contact covering the entire end of Ge NWs, the depletion region width will be increased as the NW radius is scaled down.…”
Section: The Effect Of Current Crowdingmentioning
confidence: 98%
“…There are several possible mechanisms corresponding to the deviation such as tunneling, image force lowering, carrier recombination in the depletion region and interface states. Firstly, the effect of carrier recombination in the depletion region on the I-V curve at the forward bias is not significant for our samples, because the number of recombination centers is very small in the space-charge region at the nanometer scale [20]. The effect of interface states also can be ruled out, because our high resolution transmission electron microscope observations show that the nanocontacts formed between ErSi 2 nanoislands and Si(0 0 1) substrate have no interface layer.…”
Section: The Transport Mechanisms Of Nanosized M-s Interfacementioning
confidence: 99%